Global Problems and the Experience of Coexistence of Islamic Culture - Babashli, Mammadali (Scholarya Demo Journal of Ruby, 2021)
Natural disasters, plunder of natural resources, environmental pollution, lethal diseases, and epidemics are among the global issues that the world community has been unable to address in recent years. The unconscious steps taken by humankind in relation to the Earth, the degraded ecosystem, global warming, the problem of drinking water and fresh air, the shortage of food and the problem of hunger threaten the future of humankind. The wars of aggression, frozen local conflicts and terrorism have made the modern world uninhabitable. Unemployment is on the rise, as is income inequality, chauvinism, radicalism, extraordinary cruelty, widespread illiteracy, and grave human rights violations. As a result of armed conflicts and civil wars in many parts of the world, millions of people have become refugees, starved and miserable. The influx of millions of migrants to the West has led to an unprecedented humanitarian tragedy. This situation in interstate relations has spread to societies and individuals. Differences became confrontations in wealth, the concept of "us" became the concept of "I," and tolerance in "us" became intolerance in "I" Globalization has caused societal shifts that have resulted in the emergence of differentiated identities. The aim of this study is to explore the possibility of using the experience of Islamic culture to coexist in order to find a way out of the situation. The solution for global problems is to unite efforts and try to find common ways out. The only choice is to emphasize the formation of "islands of peace" through dialogue and tolerance. The way to continue their existence is to instill the idea that existing cultures should support each other. This research describes the centuries-old experience of different religions and nations in Azerbaijan living in peace.